Constitutively high levels of endogenous soluble ST2 inhibit food allergic responses in mice - Mayuki Kojima; Kumi Izawa; Tomoaki Ando; Keiko Maeda; Ayako Kaitani; Nobuhiro Nakano; Risa Yamamoto; Shunichi Miyazaki; Mayu Shinagawa; Mio Sasaki; Anna Kamei; Akie Maehara; et al. (Proceedings of the National Academy of Sciences, 2026)
IL-33-induced signals via membrane-bound ST2 (ST2L) are critical for allergies. However, the physiological role of endogenous soluble ST2 (sST2) remains elusive. Here, we generated sST2-deficient mice with intact ST2L using the CRISPR/Cas9 system. Skin fibroblasts constitutively released sST2 protein at extremely high levels compared to mast cells, which did not reflect the expression levels of sST2 mRNA. This discrepancy can be partly explained by the sST2 protein degradation mediated by mast cell proteases. Accordingly, sST2 deficiency did not affect IL-33- and/or IgE plus antigen-stimulated mast cell activation in vitro. We provided evidence that constitutively high levels of sST2 suppress food allergies in mice by inhibiting IL-33-dependent, both expansion of jejunum mast cells and enhancement of their degranulation. Analysis of bone marrow chimeric mice under steady-state conditions showed that circulating sST2 was derived almost equally from hematopoietic and nonhematopoietic cells. Increased circulating sST2 in food-allergic mice was possibly and partly derived from fibroblasts stimulated by locally released IL-4 and IL-13. In conclusion, endogenous sST2 contributes to the suppression of food allergies.